Prediction of the operative time for hysteroscopic myomectomy for leiomyomas penetrating the intramural cavity using leiomyoma weight and clinical characteristics of patients. (30th September 2018) - Isono, Wataru; Wada‐Hiraike, Osamu; Sugiyama, Ryo; Maruyama, Masanori; Fujii, Tomoyuki; Osuga, Yutaka
Abstract: Purpose: To preoperatively predict the operative time (OT) for hysteroscopic myomectomy for G1 or G2 leiomyoma based on leiomyoma weight. Methods: The data from 544 patients who underwent one‐step hysteroscopic myomectomy were analyzed retrospectively. A total of 340 patients with leiomyoma penetrating the intramural cavity were identified as suitable candidates for calculation of the OT based on leiomyoma weight; we considered leiomyoma weight to be the most objective parameter for evaluating leiomyoma tissues. Additionally, 460 patients with a single leiomyoma were analyzed to estimate the weight of the resected leiomyoma based on its diameter. Results: Considering total leiomyoma weight (TLW) and two additional coefficients (1.5: G2 leiomyoma, 0.75: vaginal parity of the patient), we demonstrated that our formula correlated well with OT ( R 2 = 0.72). TLW also correlated well with the cube of the average diameter (AD) of leiomyomas ( R 2 = 0.89). Predicting TLW significantly improved the application of specific coefficients depending on its value (1.0: AD 0.1‐2.0 cm, 0.8: AD 2.1‐3.0 cm, 0.7: AD 3.1‐5.7 cm). Conclusion: The OT for hysteroscopic myomectomy of intracavital leiomyoma can be predicted prior to surgery using simple clinical information of the target leiomyoma and the patient. Abstract : After predicting the leiomyoma weight by multiplying the cube of average diameter of leiomyoma and considering two coefficients, we could estimate difficulty of hysteroscopic myomectomy.